In situ debris–cement admixture testing in alpine wild creeks, Taiwan. Issue 5 (10th May 2019) - Chen, Jun-Yang; Chen, I-Hui; Su, Miau-Bin
Abstract : This study explores a new method of in situ debris–cement mixing through laboratory and field experiments to reuse dredged post-disaster debris for the ground improvement of banks in alpine wild creeks, Taiwan. Different mixing ratios of water, cement and in situ debris were subjected to laboratory and field testing so that the relationships between the compressive strength, water–cement–aggregate ratio and sand content of the test specimens could be determined. The results were then applied to fieldwork in wild creeks. Furthermore, the compressive strength desired for ground improvement in alpine wild creeks through the mixing method is proposed. Considering cost-effective conditions, a cement–aggregate ratio of 1:12, compressive strength of 400–1200 psi (2·76–8·27 MPa), slump of approximately 15 cm and sand content of less than 60% are proposed. Overall, the in situ debris–cement mixing method can be practically employed for debris recycling and ground improvement to protect banks in alpine wild creeks.